Crossed cerebellar diaschisis in patients with acute middle cerebral artery infarction: Occurrence and perfusion characteristics. Issue 4 (April 2016) - Sommer, Wieland H; Bollwein, Christine; Thierfelder, Kolja M; Baumann, Alena; Janssen, Hendrik; Ertl-Wagner, Birgit; Reiser, Maximilian F; Plate, Annika; Straube, Andreas; von Baumgarten, Louisa
We aimed to investigate the overall prevalence and possible factors influencing the occurrence of crossed cerebellar diaschisis after acute middle cerebral artery infarction using whole-brain CT perfusion. A total of 156 patients with unilateral hypoperfusion of the middle cerebral artery territory formed the study cohort; 352 patients without hypoperfusion served as controls. We performed blinded reading of different perfusion maps for the presence of crossed cerebellar diaschisis and determined the relative supratentorial and cerebellar perfusion reduction. Moreover, imaging patterns (location and volume of hypoperfusion) and clinical factors (age, sex, time from symptom onset) resulting in crossed cerebellar diaschisis were analysed. Crossed cerebellar diaschisis was detected in 35.3% of the patients with middle cerebral artery infarction. Crossed cerebellar diaschisis was significantly associated with hypoperfusion involving the left hemisphere, the frontal lobe and the thalamus. The degree of the relative supratentorial perfusion reduction was significantly more pronounced in crossed cerebellar diaschisis-positive patients but did not correlate with the relative cerebellar perfusion reduction. Our data suggest that (i) crossed cerebellar diaschisis is a common feature after middle cerebral artery infarction which can robustly be detected using whole-brain CT perfusion, (ii) its occurrence is influenced by location and degree of the supratentorial perfusion reduction rather than infarct volume (iii) other clinical factors (age, sex and time from symptom onset) did not affect the occurrence of crossed cerebellar diaschisis.